The Use of Cake Application in Teaching Listening Skills: Pre-Experimental Research on the Tenth-Grade Students of SMAN 2 Teluk Keramat in Academic Year 2024/2025 - Novita, Dea; Regina, Regina; Wardah, Wardah (Journal of English Language and Education, 2025)
Listening skills are fundamental abilities in English language learning, which include the ability to accurately receive, understand, and interpret spoken language. The aspects of listening assessed in this study were identifying main ideas, identifying specific information, making inferences, and spelling vocabulary. The Cake application is a language learning platform designed to support foreign language acquisition. Some features that can be used to teach students’ listening skills are video lessons, quizzes, and video history. In this research, only the teacher used the Cake application during lessons, while students were not permitted to access or use the application either during or outside classroom hours. This approach was intended to maintain instructional control and ensure that improvements resulted from guided use rather than independent practice. This research aims to investigate the effect of the use of Cake application in teaching listening skill and to find out the effect size of its implementation. This research uses a pre-experimental design with one-group pre-test and post-test. The research participants were tenth-grade students at SMAN 2 Teluk Keramat and the sample was selected using cluster random sampling which consisted of 28 students. The data was collected using tests given to students before and after the treatment. The results showed an increase in the average score from 68.21 on the pre-test to 75.18 on the post-test. The Wilcoxon Signed-Rank test showed a statistically significant difference between the pre-test and post-test (T = 17.5 t-critical = 46). The effect size value was 0.72, which indicates a large effect. This finding concludes that the use of the Cake application in teaching listening skill has a significant effect, therefore the Cake application can be used as an alternative medium for teaching English in the classroom